1989
DOI: 10.1002/pros.2990150408
|View full text |Cite
|
Sign up to set email alerts
|

Cultured human prostate‐derived fibroblasts produce a factor that stimulates their growth with properties indistinguishable from basic fibroblast growth factor

Abstract: Fibrostromal proliferation is believed to be important in the development of benign prostatic hyperplasia (BPH). We found that a mitogen for cultured mesodermal-derived cells was present in extracts of BPH tissue. The mitogen was identified as basic fibroblast growth factor (bFGF). Previous studies did not determine the cell population(s) responsible for bFGF production in the prostate. This information is important to the understanding of the role of bFGF in the etiology of BPH. Human prostate-derived fibrobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
5

Year Published

1992
1992
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 16 publications
3
42
0
5
Order By: Relevance
“…The stimulation of tumour cell growth in conditioned medium is consistent with the secretion of stimulatory fibroblast derived growth factors and/or the inability to produce active growth inhibitory factors (Clemmons et al, 1981;Clemmons, 1984;Story et al, 1989;Yee et al, 1988). We have also shown a high proliferation effect of human skin tissue derived fibroblast C-SFM on MCF-7 cells.…”
Section: Discussionsupporting
confidence: 73%
“…The stimulation of tumour cell growth in conditioned medium is consistent with the secretion of stimulatory fibroblast derived growth factors and/or the inability to produce active growth inhibitory factors (Clemmons et al, 1981;Clemmons, 1984;Story et al, 1989;Yee et al, 1988). We have also shown a high proliferation effect of human skin tissue derived fibroblast C-SFM on MCF-7 cells.…”
Section: Discussionsupporting
confidence: 73%
“…bFGF regulates cellular growth and differentiation by involving protein kinase C (Hrzenjak and Shain, 1997), mitogen-activated protein kinase (Hurley et al, 1996;Milasincic et al, 1996), phosphatidylinositol 3-kinase (Raffioni and Bradshaw, 1992) or phospholipase signalling (Sa and Fox, 1994;Suzuki et al, 1996). bFGF was identified as a major autocrine growth factor produced by prostate fibroblasts (Story et al, 1989). In later studies, it was demonstrated that prostate epithelial cells are also a source of bFGF (Nakamoto et al, 1992;Sherwood et al, 1992;Cronauer et al, 1997a).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that urogenital sinus mesenchyme plays a major role in the (androgen-induced) development of the gland (Cunha et al, 1987); subsequently it was shown that these interactions may have retained their integral role in the adult prostate (Cunha et al, 1987;Chung et al,1991a,b (Thompson, 1990;Story, 1991), and some of these have been positively identified as being produced (also) by stromal cells, suggesting a role in stromal-epithelial interactions (Story et al, 1989;Djakiew et al, 1991;Gleave et al, 1992). The fact, however, that prolonged androgen administration to castrated animals does not induce the gland to grow beyond its predetermined size (Sugimura et al, 1986), together with the observation that withdrawal of androgens decreases epithelial cell number only in the in vivo situation where stroma is present (Isaacs, 1984;McKeehan et al, 1984), suggests a role for stromally derived epithelial cell growth inhibitors.…”
Section: Discussionmentioning
confidence: 99%